Comparative analysis of dermal and inhalation exposures to antineoplastic drugs among workers in the workplaces: a systematic review - Zahra Beigzadeh; Farideh Golbabaei; Fariborz Omidi; Seyed Jamaleddin Shahtaheri (BMC Public Health)
Abstract Objective Occupational exposure to antineoplastic drugs presents significant health risks to workers, necessitating a comprehensive understanding of both dermal and inhalation exposures. This systematic review examines the relative significance of cutaneous versus inhalation exposure among professionals handling these potent medications. Study design Systematic review. Methods A systematic search using the PECO framework was conducted in PubMed, Scopus, and Web of Science, adhering to PRISMA guidelines. Data from surface and air sampling studies were collected and analyzed. Results Ten studies met the inclusion criteria, assessing various antineoplastic drugs across different occupational settings. Surface contamination levels varied widely, with concentrations ranging from very low to high, whereas airborne monitoring consistently reported "Not Detectable" levels. Exposure levels were influenced by workplace practices, handling procedures, and the sensitivity of detection methods. Conclusions This systematic review of ten studies on dermal and inhalation exposure to antineoplastic drugs in various occupational settings reveals significant variability in contamination levels. Tailored safety measures, including stringent protocols, decontamination procedures, and respiratory protection, are essential for workplace safety. The review highlights the importance of standardized safety protocols, considering the impact of workplace practices and detection method sensitivity. Additionally, it underscores the health risks associated with even low-level exposure, emphasizing the need for biological monitoring. Despite some limitations, this study offers valuable insights for enhancing the safety of staffs handling these potent drugs, guiding future research and policy development.